Respiratory allergy to moth: the importance of sensitization to Bombyx mori in children with asthma and rhinitis - Laura M.L. Araujo; Nelson A. Rosário Filho; Carlos A. Riedi (Elsevier, 2014)
Objective: this study aimed to prepare a silkworm moth (Bombyx mori) antigenic extract and to perform skin prick tests with this extract in patients with allergic respiratory diseases; to evaluate serum specific immunoglobulin E (IgE) to Bombyx mori using ImmunoCAP® system and to report the frequency of positivity between the two methods and with clinical data. Methods: this was a cross‐sectional study with 99 children and adolescents diagnosed with asthma and/or allergic rhinitis, who had skin reactivity to at least one of the six aeroallergens tested. Clinical data were evaluated: skin prick tests with Bombyx mori in‐house extract, and total and specific IgE analysis using ImmunoCAP® were performed. Results: the frequency of Bombyx mori specific IgE was found to be 52.5% and 60% using the skin prick test and ImmunoCAP®, respectively. An association between a positive skin test for Bombyx mori and the presence of allergic rhinitis, atopic dermatitis, and urticaria was observed, but the same was not true for asthma or allergic conjunctivitis. There was no relation with the severity of asthma or rhinitis symptoms. Conclusions: a high frequency of sensitization to Bombyx mori was observed in a selected population of patients with respiratory allergic diseases in the city of Curitiba, state of Paraná, Brazil. The extract prepared from the wings of this moth species is effective in demonstrating this sensitivity. Resumo: Objetivo: Preparar extrato antigênico da mariposa do bicho‐da‐seda (Bombyx mori) e realizar testes cutâneos com esse extrato em pacientes com doenças respiratórias alérgicas, avaliar IgE sérica específica para Bombyx mori usando o sistema ImmunoCAP® e relatar a frequência de positividade entre os dois métodos e com dados clínicos. Métodos: Estudo transversal com 99 crianças e adolescentes com diagnóstico de asma e/ou rinite alérgica, que apresentaram reação cutânea a pelo menos um dos seis aeroalérgenos testados. Os dados clínicos foram avaliados; testes cutâneos com extrato de Bombyx mori e análise de IgE total e específica por ImmunoCAP® foram realizados. Resultados: A frequência de IgE específica para Bombyx mori foi de 52,5% e 60%, respectivamente, pelo teste cutâneo e ImmunoCAP®. Foi observada uma associação entre o teste cutâneo positivo para Bombyx mori e a presença de rinite alérgica, dermatite atópica e urticária, mas o mesmo não ocorreu para a asma ou conjuntivite alérgica. Não houve relação com a gravidade dos sintomas de asma ou rinite. Conclusões: Alta frequência de sensibilização à Bombyx mori foi encontrada em uma população selecionada de pacientes com doenças alérgicas respiratórias na cidade de Curitiba, estado do Paraná, Brasil. O extrato preparado a partir das asas dessa espécie de mariposa é eficaz em demonstrar essa sensibilidade. Keywords: Sensitization, Moth, Asthma, Rhinitis, Palavras‐chave: Sensibilização, Mariposa, Asma, Rinite